La función del modo narrativo tú frente al factor autobiográfico (yo y él) en La muerte de Artemio Cruz - Rodríguez Mansilla, Fernando (Verbum – Analecta Neolatina, 2005)
In Carlos Fuentes’s work we can witness, as with many other Boom writers, the proposal of a novel innovation through subverting traditional writing genres. Specifically, in La Muerte de Artemio Cruz, there seems to be an opposition between the narrative voice TÚ and the narrative voices YO and ÉL in order to establish a destruction of the conventional autobiographical discourse that the last two represent. In addition, TÚ openly denounces the chingada, an essential element of the Mexican social life which YO and ÉL defend and justify, so Fuentes goes beyond the proposed stylistic goal. Otherwise, after Aura, where the author introduces the TÚ form for the first time, the complex plot of Artemio Cruz’s agony results in the success of the ’New Latin American Novel’.